The Analysis of Marketing Strategy to Improve the Competitive Positioningof the Craft Industry in Gorontalo - Tineke Wolok (AIBPM Publisher, 2021)
This research analyzes the mapping of the potential marketing strategy to improve the competitive positioning of craft industries in Gorontalo and elucidates the appropriate marketing strategy to improve their competitive positioning. This research applied a descriptive quantitative approach in mapping the problems and designing the appropriate strategy. Also, an analytical hierarchy process was conducted to examine underlying factors to develop the craft industries. The result of the analysis shows that in addition to products, promotion, prices, and processes occupy a significant role in enhancing the industry competitiveness.